2014
DOI: 10.1371/journal.pone.0102827
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Artificial Blue-Enriched White Light Is an Effective Countermeasure to Delayed Circadian Phase and Neurobehavioral Decrements

Abstract: Studies in Polar Base stations, where personnel have no access to sunlight during winter, have reported circadian misalignment, free-running of the sleep-wake rhythm, and sleep problems. Here we tested light as a countermeasure to circadian misalignment in personnel of the Concordia Polar Base station during the polar winter. We hypothesized that entrainment of the circadian pacemaker to a 24-h light-dark schedule would not occur in all crew members (n = 10) exposed to 100–300 lux of standard fluorescent white… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
37
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 55 publications
(58 reference statements)
4
37
0
2
Order By: Relevance
“…In Antarctica 17000 K blue-enriched light throughout the wake period advanced the circadian system (as assessed by the urinary melatonin metabolite, 6-sulphatoxymelatonin) accompanied by earlier actigraphic sleep onset and shorter sleep latency during the winter [28]. Also in Antarctica normal fluorescent light of 100-300 lux showed a significant delay in melatonin onset compared to blue-enriched white light with no difference in rest-activity rhythms by NCPRA under the two light conditions [29]. Similarly, a recent study reported cognitive improvements using an assessment of cognitive function and a profile of mood states with 30 minutes of blue LED light (400 lux) each day compared to red light in older people in long term care [75].…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations
“…In Antarctica 17000 K blue-enriched light throughout the wake period advanced the circadian system (as assessed by the urinary melatonin metabolite, 6-sulphatoxymelatonin) accompanied by earlier actigraphic sleep onset and shorter sleep latency during the winter [28]. Also in Antarctica normal fluorescent light of 100-300 lux showed a significant delay in melatonin onset compared to blue-enriched white light with no difference in rest-activity rhythms by NCPRA under the two light conditions [29]. Similarly, a recent study reported cognitive improvements using an assessment of cognitive function and a profile of mood states with 30 minutes of blue LED light (400 lux) each day compared to red light in older people in long term care [75].…”
Section: Discussionmentioning
confidence: 91%
“…Blue-enriched polychromatic light has now been tested in a number of settings [27][28][29][30], but caution should be applied to the findings, as in some cases, such as the study of older people reported here, the effects appear small and mixed. Based on this work it is important to further characterise the risks and benefits of 17000 K blue-enriched light prior to this lighting being applied permanently in care homes for older people.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The spectral sensitivity associated with the suppression of nocturnal melatonin in humans by light has been investigated and action spectra constructed that show distinct short‐wavelength sensitivity peaking between 460 and 490 nm . An interesting study was conducted with participants at a polar base station (where there is no access to sunlight in winter) where sleep problems and circadian misalignment are often reported . A combination of measurements of melatonin levels (from saliva samples) and self‐reporting was used to assess the effects of standard fluorescent white lights and blue‐enriched lights in the daytime and showed that blue‐enriched light resulted in substantially less delay in the onset of melatonin in the evening .…”
Section: Circadian Entrainment and Disruptionmentioning
confidence: 99%
“…Ao longo dos últimos 10 anos (2006 a 2017), foram publicados menos de 30 estudos especializados, conforme consulta às bases de dados Web of Science e SCOPUS. As publicações mais recentes focam em estresse e coping (Anton-Solanas, O'Neil, Morris & Dunbar, 2016;Barkaszi, Takács, Czigler & Balázs, 2016); aspectos relacionados ao sono e ao ciclo circadiano (Brockmann et al, 2017;Chen, Wu, Li, Zhang & Xu, 2016;Feuerecker et al, 2014;Morris, Pilcher, & Powell, 2017); e à adaptação ao ambiente polar (Jin, Touyama, Yamada, Yamazaki, & Benno, 2014;Najjar et al, 2014;Pattarini, Scarborough, Sombito, & Parazynski, 2016).…”
unclassified